Racecadotril for acute diarrhoea in children: systematic review and meta-analyses. Issue 3 (29th December 2015) - Gordon, Morris; Akobeng, Anthony
Abstract : Objective: Racecadotril is an antisecretory agent that can prevent fluid/electrolyte depletion from the bowel as a result of acute diarrhoea without affecting intestinal motility. An up-to-date systematic review is indicated to summarise the evidence on racecadotril for the treatment of acute diarrhoea in children. Design: A Cochrane format systematic review of randomised controlled trials (RCTs). Data extraction and assessment of methodological quality were performed independently by two reviewers. Methodological quality was assessed using the Cochrane risk of bias tool. Patients: Children with acute diarrhoea, as defined by the primary studies. Interventions: RCTs comparing racecadotril with placebo or other interventions. Main outcome measurs: Duration of illness, stool output/volume and adverse events. Results: Seven RCTs were included, five comparing racecadotril with placebo or no intervention, one with pectin/kaolin and one with loperamide. Moderate to high risk of bias was present in all studies. There was no significant difference in efficacy or adverse events between racecadotril and loperamide. A meta-analysis of three studies with 642 participants showed significantly shorter duration of symptoms with racecadotril compared with placebo (mean difference −53.48 h, 95% CI −65.64 to −41.33). A meta-analysis of five studies with 949 participants showed no significant difference in adverse events between racecadotril and placebo (risk ratio 0.99, 95% CI 0.73 to 1.34). Conclusions: There is some evidence that racecadotril is more effective than placebo or no intervention in reducing the duration of illness and stool output in children with acute diarrhoea. However, the overall quality of the evidence is limited due to sparse data, heterogeneity and risk of bias. Racecadotril appears to be safe and well tolerated.